Traumatic asphyxia - Montes Tapia, Fernando Félix; Barreto Arroyo, Itzel; Cura Esquivel, Idalia Aracely; Rodríguez Taméz, Antonio; O Cavazos, Manuel Enrique de la (Lippincott Williams & Wilkins, 2014)
Traumatic asphyxia is a rare condition in children that usually occurs after severe compression to the chest or abdomen. We report 3 cases in patients 18, 20, and 36 months of age who presented signs and symp- toms of traumatic asphyxia after car accidents. Two clinical features were consistent in all 3 patients: multiple petechiae on the face and bulbar conjunctival hemorrhage; 2 patients had facial cyanosis, and 1 had facial edema. In children, the number of clinical manifestations that should be evi- dent to diagnose traumatic asphyxia has not been ascertained. However, in any history of trauma with compression of the chest or abdomen and signs of increased intravenous craniocervical pressure, traumatic asphyxia should be suspected.